POST-INDUSTRIAL SOCIETY AS A TRANSITIONAL PERIOD TO NEW SOCIAL AND ECONOMIC SYSTEM - M. N. Rosenko; A. A. Kumpen (Дискурс, 2016)
Reasons for the main content of the modern era as a transition period from capitalism and socialism to new type of social reality are provided in the article. The features of the present transitional stage are its global nature, forming of post-industrial society, development of high-technology material and spiritual production, emergence of a new class paradigm of social relations, deepening of social inequality, aggravation of internal and external contradictions.